Analysis of the Influence of Monetary Instrument on the Real Sector: Using Industrial Production Index (IPI) Approach - Ahmad Suminto; Risma Nada Azkiya (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The role of the monetary sector in Indonesia's economic growth is very important by minimizing transaction costs or information in financial markets, to ensure the smooth flow of economic activities and enhance the productivity of individuals in the production of goods and services in the real sector. The purpose of this study is to determine the influence of monetary instruments on the real sector using Industrial Production Index (IPI) approach. This research uses quantitative methods with an Autoregressive Distributed Lag (ARDL) estimation model, with Bank Indonesia Certificates (SBI), Interbank Money Market (PUAB) and credit as independent variables of monetary instruments, while Industrial Production Index (IPI) as the dependent variable. The results of this research show that the variable SBI in this research had in-significant results on IPI. Therefore, SBI in this research has no influence on IPI. Variable interbank money market the result of this research is that the interbank variable has an influence on IPI. The variable credit for the results of this study is in-significant. Thus, credit variables have no effect on IPI. Based on the results of the f-test on monetary instruments, it can be described that instruments from monetary have a probability value of 0.0013 < 0.05. The coefficient of determination test on the monetary instruments, it can be described that monetary instruments have an influence of 45.53%, where the influence comes from SBI, interbank money market and credit variables as monetary instrument variables.